2011
DOI: 10.1128/jvi.02216-10
|View full text |Cite
|
Sign up to set email alerts
|

The Breadth and Potency of Passively Acquired Human Immunodeficiency Virus Type 1-Specific Neutralizing Antibodies Do Not Correlate with the Risk of Infant Infection

Abstract: Although a major goal of human immunodeficiency virus type 1 (HIV-1) vaccine efforts is to elicit broad and potent neutralizing antibodies (NAbs), there are no data that directly demonstrate a role for such NAbs in protection from HIV-1 infection in exposed humans. The setting of mother-to-child transmission provides an opportunity to examine whether NAbs provide protection from HIV-1 infection because infants acquire passive antibodies from their mothers prior to exposure to HIV-1 through breastfeeding. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 57 publications
7
50
1
Order By: Relevance
“…Although this is in contrast to previous results in subtype Binfected women (12), a recent study has yielded results similar to ours in that the neutralization breadth of maternal antibodies measured in infant samples did not correlate with protection from infection (36). Higher breadth of maternal neutralizing antibodies, at least for women infected with non-B subtypes, has thus shown no correlation with protection from MTCT.…”
Section: Discussioncontrasting
confidence: 57%
“…Although this is in contrast to previous results in subtype Binfected women (12), a recent study has yielded results similar to ours in that the neutralization breadth of maternal antibodies measured in infant samples did not correlate with protection from infection (36). Higher breadth of maternal neutralizing antibodies, at least for women infected with non-B subtypes, has thus shown no correlation with protection from MTCT.…”
Section: Discussioncontrasting
confidence: 57%
“…However, not all studies established this association (2,3). Several studies reported more potent HIV-1-neutralizing Ab responses in nontransmitting mothers compared with those in transmitting mothers (4) as well as transmission of neutralization escape variants (5)(6)(7)(8), yet other studies did not (9)(10)(11). These disparate results may be due to small cohort sizes, distinct timing of infant HIV-1 diagnosis, and inadequate control of major nonimmune risk modifiers of transmission.…”
Section: Introductionmentioning
confidence: 55%
“…Other recent MTCT studies focused on postnatal transmission and the role of maternal antibodies (18,31). The former one compared Env-specific IgG and IgA in serum and breast milk specimens from 41 HIV-positive women; the IgG fraction from breast milk showed neutralizing and ADCC activities that were 100-fold higher than the IgA ones, and similar differences were observed in serum (15).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the role and extent of other antibody-mediated antiviral activities, such as ADCC, were not addressed in those studies (31). In our study, not only different antibody titers but also different pools of antibodies may exist, with pools being reactive to the MPER or the IDE domains and some of the IgGs displaying virus-neutralizing properties (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation